Development of Digital-Based Bleep Test Tools - Ramdani, Aril; Rahmat, Dadan (CV. Publikasi Indonesia, 2024)
In the world of sports, technology has become essential to improve the accuracy and efficiency of measuring athletes' fitness. The bleep test, a popular method for measuring cardiovascular endurance, often suffers from accuracy issues when performed manually. The purpose of this research is to develop a digital-based bleep test tool. In the implementation of the bleep test, there is currently no tool that ensures that bleep test participants pass the specified distance, and recording is still manual. This bleep test aid uses an ultrasonic sensor to detect test participants during the bleep test, and the data from this sensor will be sent to a PC or laptop to display the test results. This research method uses the R&D research method with the Borg and Gall research model. The result of this research is a sensor tool to help record the implementation of the bleep test digitally. The results of the operational field test of this tool are able to detect test participants in the implementation of the bleep test and send data on the level, rotation, and Vo2max of participants in the implementation of the bleep test.